ЎҚУВ МАШҒУЛОТЛАРИДА БЎЛАЖАК МЕҲНАТ ТАЪЛИМИ ЎҚИТУВЧИЛАРИНИНГ ИНДИВИДУАЛ ИШИНИ ТЎҒРИ ТАШКИЛ ЭТИШ - Джумагулов, З.У. (SCIENCE and SOCIETY, 2018)
The article reveals the factors of the correct organization of individual work of future teachers of labor education, the perception of knowledge, the understanding and generalization of this knowledge. The author of the article also studies the issues of content nature and complexity of the material, , didactic goals of the lesson, the means of training, the definition of the initial knowledge of future teachers of labor education.
Keywords: таълим; ўқитувчи; бўлажак меҳнат таълими ўқитувчилари; билим; метод; ўқитишни индивидуаллаштириш; режалаштириш; касбий маҳорат; касбий қизиқиш; амалиёт